Nuclear deformation mediates liver cell mechanosensing in cirrhosis - Guixé-Muntet, Sergi (JHEP Rep, 2020)
BACKGROUND & AIMS: Liver stiffness is increased in advanced chronic liver disease (ACLD) and accurately predicts prognosis in this population. Recent data suggest that extracellular matrix stiffness per se may modulate the phenotype of liver cells. We aimed at investigating the effect of matrix stiffness on the phenotype of liver cells of rats with cirrhosis, assessing its influence on their response to antifibrotic strategies and evaluating associated molecular mechanisms. METHODS: Hepatocytes, hepatic stellate cells, and liver sinusoidal endothelial cells were isolated from healthy rats or rats with cirrhosis (carbon tetrachloride or thioacetamide), and cultured on polyacrylamide gels with different physiologically relevant stiffness for 72 h. RESULTS: All cell types of rats with cirrhosis cultured at low stiffness showed a significant phenotype amelioration vs. rigid matrix (assessed by quantitative morphology, mRNA expression, protein synthesis, and electron microscopy imaging). Additionally, stiffness modified the antifibrotic effects of liraglutide in stellate cells of rats with cirrhosis. Finally, evaluation of nuclear morphology revealed that high stiffness induced nuclei deformation in all cell types, an observation confirmed in cells from human livers. Disconnecting the nucleus from the cytoskeleton by cytoskeleton disruption or a defective form of nesprin 1 significantly recovered spherical nuclear shape and quiescent phenotype of cells. CONCLUSIONS: The environment's stiffness per se modulates the phenotype of healthy rats and liver cells of rats with cirrhosis by altering the nuclear morphology through cytoskeleton-derived mechanical forces. The reversibility of this mechanism suggests that targeting the stiffness-mediated intracellular mechanical tensions may represent a novel therapeutic strategy for ACLD. LAY SUMMARY: During cirrhosis, the liver becomes scarred, stiff, and unable to perform its normal functions efficiently. In this study, we demonstrated that cells from diseased (stiff) livers recovered their functionality when placed in a soft environment (as that of a healthy liver). Furthermore, treatments aimed at tricking liver cells into believing they are in a healthy, soft liver improved their function and could potentially contribute to treat cirrhosis.